Analisis Determinan Status Kemiskinan Rumah Tangga Sektor Pertanian Di Nusa Tenggara Timur Tahun 2020 - Risnawati Azali; Titik Harsanti (Politeknik Statistika STIS, 2022)
Poverty is a problem faced by the whole world, especially developing countries. As a developing country, Indonesia prioritizes poverty alleviation in the Sustainable Development Goals (SDGs) and RPJMN 2020-2024, particularly in East Nusa Tenggara (NTT) as the province with the third highest percentage of poor people in Indonesia. Therefore, the purpose of this study is to analyze poor households in the agricultural sector in NTT in 2020, considering that most of the poor households in NTT come from the agricultural sector. The results of binary logistic regression analysis using Susenas March 2020 data indicate that the age of the head of household (KRT), education of the household head, number of household members, access to business credit, internet access, and the agricultural sub-sector have a significant effect, while gender and land ownership have no significant effect on status. household poverty in the agricultural sector in NTT in 2020. To overcome poverty in agricultural households in NTT, the government needs to evaluate the 12-year compulsory education program and family planning with enough 2 children in NTT considering that the tendency to become poor is greater in households with KRT education from junior high school to senior high school. below, the minimum number of ART is 4 and the age of the head of household is younger. In addition, it is necessary to develop agricultural businesses in more productive sectors with easy access to business credit and the TIK to reach a wider market